ARABIC-A STUDY OF METHODOLOGY OF IMAM MALIK IN MUWAṬṬA - Abdul Hia Madni; Imtiaz Bibi (دی اسکالر)
The source of three schools of Suni jurisprudence is identified as the book of Muwatta. One of the scholars who agree with this supposition is Shah Waliullah who considers it as the foundation of all four schools and states that Muwatta’s text is a commentary on these schools (Ambiguous). Our beloved Prophet Muhammad (PBUH) was a follower of many norms, beliefs and practices which are all enshrined in the book. So it can be said that the compilation of the book took great effort and due diligence on the part of its authors. It took Imam Malik forty years to compile the book of 'Muwatta' as a manifestation of the "well-trodden path" taken by the citizens of Madina. The name of the book is translated to ‘agreed upon by many’ which means that the people of Madina unanimously agreed upon it. It has such a high accord that people of every school of Fiqh and all of the imams of hadith scholarship are mutually united on its genuine accounts. The conditions which were followed by the Imam while compiling his book are among the most reliable and authentic. He followed a method of erring on the side of caution and choosing only sound reports. Hence, many of the isnaads (chains) of Imam Malik are of the highest standard of Saheeh. Due to this, Imam Bukhaari and Muslim were found to narrate most of his hadeeths in their books. Thee method of compilation in the book was contemporary to the present times, so he compiled the Hadiths with the words of the companions of Prophet Muhammad (PBUH) and Taabi’een (who came after them) and legal opinions (Ambiguous). There are 613 reports by companions and 285 by Taabieen (Ambiguous). In one chapter the Hadiths are mentioned foremost and then followed by the reports of the Sahaabah and Taabi’een while at other times, the actions of the people of Madina are quoted so his book is a book of Fiqh and Hadith at the same time and cannot be categorized as a book of reports only. We also find that it is limited to sections on Fiqh, etiquette and the actions of day and night. However, it lacks information on Tauheed, zuhd (asceticism), the Resurrection, stories and tafseer.